2016
DOI: 10.2147/pgpm.s115741
|View full text |Cite
|
Sign up to set email alerts
|

Treatment-resistant schizophrenia: current insights on the pharmacogenomics of antipsychotics

Abstract: Up to 30% of people with schizophrenia do not respond to two (or more) trials of dopaminergic antipsychotics. They are said to have treatment-resistant schizophrenia (TRS). Clozapine is still the only effective treatment for TRS, although it is underused in clinical practice. Initial use is delayed, it can be hard for patients to tolerate, and clinicians can be uncertain as to when to use it. What if, at the start of treatment, we could identify those patients likely to respond to clozapine – and those likely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
97
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(102 citation statements)
references
References 170 publications
(166 reference statements)
1
97
0
4
Order By: Relevance
“…What if, at the early stages of antipsychotic treatment we could identify those patients likely to respond to clozapineand those likely to have adverse effects? The available neuroimaging and genetic biomarkers cannot yet reliably guide the early use of clozapine (Lally et al, 2016b, Samanaite et al, 2018. Of 379 investigated gene variants, only three (DRD3 Ser9Gly, HTR2A His452Tyr, and C825T GNB3) have independently replicated significant findings in clozapine response prediction.…”
Section: Predicting Trs / Clozapine Respondersmentioning
confidence: 99%
“…What if, at the early stages of antipsychotic treatment we could identify those patients likely to respond to clozapineand those likely to have adverse effects? The available neuroimaging and genetic biomarkers cannot yet reliably guide the early use of clozapine (Lally et al, 2016b, Samanaite et al, 2018. Of 379 investigated gene variants, only three (DRD3 Ser9Gly, HTR2A His452Tyr, and C825T GNB3) have independently replicated significant findings in clozapine response prediction.…”
Section: Predicting Trs / Clozapine Respondersmentioning
confidence: 99%
“…It is well known that genetic and environmental factors contribute to the underlying cause of schizophrenia (SZ) [6673]. Recently, it was shown that the mammalian brain suffers a global epigenomic reconfiguration during fetal to young adult development which could influence SZ onset specifically before the age of 20 [11].…”
Section: Main Textmentioning
confidence: 99%
“…To date, pharmacogenetic research has emphasized the major neurotransmitter systems involved in the pharmacodynamics and pharmacokinetics of antipsychotics. While issues with consistency exist in the findings [67][68][69][70], many of these associations could still be important. Several reasons may underlie the inconsistent results, such as different duration of clozapine treatment among the studies, different inclusion criteria for clozapine responders [23], and different ethnicities [71][72][73][74].…”
Section: Pharmacogeneticsmentioning
confidence: 99%